Sponge material used for stopping bleeding and promoting osteogenesis and based on giant salamander skin secretions
By preparing sponge materials based on chitosan and salamander skin secretions, the problem that existing dental hemostasis materials cannot stop hemostatic and inhibit bone healing for a long time is solved, and the effect of effectively stopping hemostatic and promoting bone healing is achieved.
Patent Information
- Application Number
- CN202510123498.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-10
- Publication Date
- 2025-04-25
AI Technical Summary
Existing dental hemostatic materials cannot maintain the hemostatic effect for a long time, and some materials such as bone wax will inhibit bone healing and production.
Using sponge materials based on chitosan and salamander skin secretions, the solubility and biological activity of the material are improved through mechanical treatment and preparation methods in a neutral environment, and their ability to stop bleeding and promote bone healing is enhanced.
It realizes effective hemostasis of sponge materials in dental surgery, promotes bone production and healing, and avoids the inhibitory effect brought by traditional materials.
Smart Images

Figure CN119868628A_ABST
Abstract
Description
[0001] This application is a divisional application based on the Chinese invention patent application with application number 202310522221.4, application date May 10, 2023, and invention name "A sponge material based on salamander skin secretions for hemostasis and osteogenesis". Technical Field
[0002] The invention relates to the field of sponge materials, and in particular to a sponge material based on skin secretions of a salamander for hemostasis and osteogenesis, a preparation method and application thereof. Background Art
[0003] Bleeding, exudation, leakage, or other forms of fluid loss often occur during and after routine dental procedures such as endodontic or periodontal surgery, orthodontic treatment, tooth extractions, orthognathic surgery, biopsies, and other oral surgical procedures.
[0004] For example, after tooth extraction, it is necessary to quickly stop bleeding and form a blood clot on the wound in the open tooth socket. Traditionally, cotton padding or gauze is usually used to stop bleeding. Although the presence of these materials can absorb blood and fluids, they cannot stop bleeding for a long time. More importantly, these materials cannot promote healing. Although bone wax in the prior art can be left indefinitely at the implant site, many animal studies and clinical studies have shown that it inhibits bone healing and / or formation. Summary of the invention
[0005] In a first aspect, the present invention provides a method for preparing a sponge material, characterized in that the method comprises: S1: mixing chitosan powder with a first solvent and stirring to obtain a chitosan solution; In some embodiments, the first solvent includes one or more of ultrapure water, deionized water, water for injection, and pure water.
[0006] In some embodiments, the chitosan powder includes chitosan that has not been deacetylated or chitosan that has been deacetylated.
[0007] In some embodiments, the chitosan is obtained by deproteinizing and decalcifying crushed shrimp shells and / or crab shells.
[0008] In some embodiments, the deacetylation treatment comprises adding the chitosan to 40 wt.% NaOH, heating in a 100°C oil bath and stirring, then washing to neutrality and drying; wherein the degree of deacetylation of the chitosan powder is controlled by the heating time.
[0009] In some embodiments, the heating time comprises 0.5 - 4 h.
[0010] In some embodiments, the heating time includes one or more of 0.5, 1, 1.5, 2, 2.5, 3, 3.5 and 4 h.
[0011] S2 mechanically treating the chitosan solution to obtain a first chitosan dispersion, wherein the mechanical treatment comprises grinding the chitosan using an ultrafine grinder at a grinding disc gap of 0, -10, -50 and -100 μm, respectively; In some embodiments, the number of millings comprises 10 times.
[0012] In some embodiments, the rotation speed of the ultrafine grinder comprises 1500 rpm.
[0013] S3 centrifuging the first chitosan dispersion and collecting the chitosan solid in the lower layer, and then resuspending the chitosan solid with the first solvent to obtain a second chitosan dispersion; S4: mixing and stirring the second chitosan dispersion and the hydrolyzate of skin secretions of Siberian salamander under neutral conditions, and then adding a cross-linking agent to obtain a third chitosan dispersion; In some embodiments, the concentration of the second chitosan dispersion comprises 2 wt.%.
[0014] In some embodiments, the concentration of the hydrolyzate of skin secretions of Siberian salamander comprises 2 wt.%.
[0015] In some embodiments, the cross-linking agent comprises genipin.
[0016] In some embodiments, the mass ratio of the second chitosan dispersion, the hydrolyzate of skin secretions of Siberian salamander and the cross-linking agent comprises 2000:2000:1.
[0017] S5 performing a first freeze-drying treatment on the third chitosan dispersion to obtain a first sponge material; In some embodiments, the first freeze-drying treatment includes precooling at 4°C for 2 h, freezing at -20°C for 12 h, and freeze-drying for 24 h.
[0018] S6 allowing the first sponge material to stand for sufficient cross-linking, and then adding the first solvent to the first sponge material so that the first sponge material fully absorbs water, thereby obtaining a first sponge material that fully absorbs water; S7: subjecting the first sponge material that has fully absorbed water to a second freeze-drying process to obtain a second sponge material.
[0019] In some embodiments, the second freeze-drying treatment comprises freezing at -20°C for 12 h and freeze-drying for 24 h.
[0020] In a second aspect, the present invention provides a sponge material prepared by the above method.
[0021] In a third aspect, the present invention provides use of the sponge material in preparing a hemostatic material.
[0022] In some embodiments, the hemostatic material is used for hemostasis of blood vessels, organs or bones.
[0023] In some embodiments, the blood vessels include veins and arteries.
[0024] In some embodiments, the organ comprises the liver.
[0025] In a fourth aspect, the present invention provides use of the sponge material in preparing a bone hemostatic material.
[0026] In some embodiments, the bone hemostatic material is used for implantation into a bone defect site.
[0027] In some embodiments, the bone hemostatic material is used for implantation at a tooth extraction site.
[0028] In some embodiments, the bone hemostatic material is shaped and sized.
[0029] In some embodiments, the bone hemostatic material is compressed.
[0030] In some embodiments, the bone hemostatic material is used during or after dental surgery.
[0031] In some embodiments, the dental surgery includes one or more of tooth extraction, site preservation, apical surgery, GBR (guided bone regeneration), GTR (guided periodontal regeneration), periodontal surgery, orthognathic surgery, and bone defect repair.
[0032] When selecting an effective bone hemostatic material, it is necessary not only to evaluate the effectiveness, immediacy and ease of use of the material, but also to pay attention to its potential consequences, such as whether it will have an adverse effect on bone healing. Commonly used bone hemostatic materials include non-absorbable materials, such as softened beeswax; or absorbable materials made from plants (such as cellulose), animal products (such as collagen, gelatin) or synthetic polymers. However, some bone hemostatic materials in the prior art (such as bone wax) have been shown to inhibit bone growth through animal studies and clinical studies. When used for osteogenesis, the prior art often promotes bone formation by loading sponge materials with cells or growth factors (such as BMP-2) and other substances.
[0033] Chitosan has good affinity with the human body, and has the advantages of being porous, hemostatic, and antibacterial. Based on the above biological properties, chitosan can be used as a bioabsorbable sponge material for hemostasis and other scenarios. However, chitosan has poor water solubility. In fact, the prior art believes that it is difficult to prepare a neutral chitosan sponge. The prior art usually uses a weak acid solution to treat chitosan to increase its solubility, such as a low mass fraction acetic acid solution. However, under acidic conditions, it is difficult for chitosan to load bioactive factors or proteins.
[0034] The preparation method provided by the present invention adopts mechanical treatment (specifically, mechanical exfoliation of chitosan powder by ultrafine particle crusher) of chitosan powder, and maintains a neutral environment throughout the process to prepare the sponge material. This can not only promote the dissolution of chitosan powder, avoiding the negative impact on the sponge material caused by modification; but also retain the bioactive factors or protein activity in the hydrolyzate of salamander skin secretions (such as SSAD hydrolyzate), which helps to further improve the biological properties of the sponge material such as antibacterial, pro-coagulation, pro-cell proliferation, and pro-healing.
[0035] It should be emphasized that the addition of hydrolyzed salamander skin secretions can also improve the mechanical properties of the sponge material, which may be due to the addition of hydrolyzed salamander skin secretions to increase the cross-linking sites of the sponge material. Fig.10 As shown in the figure, in 100 compression-release cycles with a compressive strain of 40%, the compressive stress of the sponge material with the addition of SSAD hydrolyzate was continuously greater than that of the simple chitosan group without the addition of SSAD. After 100 cycles, the stress retention rate of the sponge material with the addition of SSAD hydrolyzate increased and the energy loss rate decreased.
[0036] In summary, the sponge material provided by the present invention can be used as a hemostatic material to stop bleeding in blood vessels (such as arteries and veins), organs (such as the liver), bones (such as during dental surgery) and wounds with small amounts of bleeding (such as abrasions). BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor.
[0038] Figure 1 The diagram is a result of evaluating the hydrophilic and hydrophobic properties of each sponge material; Figure 2A This is the evaluation result diagram of the antibacterial performance of each sponge material; Figure 2BThe direct contact antibacterial test results of each sponge material are shown in the figure; Figure 3 This is a graph showing the evaluation results of the proliferation-promoting performance of each sponge material; Figure 4A This is the hemolysis rate result diagram of each sponge material; Figure 4B This is a graph showing the evaluation results of the procoagulant performance of each sponge material; Figure 5 The in vivo hemostatic performance evaluation results of each sponge material are shown in FIG. Fig. 6A The results of two months of implantation of each experimental group in the rat alveolar defect model; Figure 6B Schematic diagram showing the preservation of the alveolar ridge contour; Figure 6C The statistical graphs of the width, height and number of trabeculae of the alveolar ridge after treatment in each experimental group; Fig.6D The degradation of each experimental group after two months of implantation; Figure 7 The SEM images of chitosan micro-nano fibers in groups with different deacetylation degrees; Figure 8 is the SEM image of the cross section of each sponge material; Fig. 9 The stress-strain curve of the sponge material CS 0.5 + SSAD after 100 compression cycles in liquid; Fig.10 This is a graph showing the maximum stress variation of each sponge material under different compression cycles. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0040] Herein "and / or" includes any and all combinations of one or more of the associated listed items.
[0041] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.
[0042] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0043] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, even more typically + / - 0.5% of the stated value.
[0044] In this specification, some embodiments may be disclosed in a format of being in a certain range. It should be understood that this description of "being in a certain range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values within this range. For example, the description of the range 1 to 6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as individual numbers within this range, such as 1, 2, 3, 4, 5 and 6. Regardless of the breadth of the range, the above rules apply.
[0045] Example 1: Preparation of the sponge material of the present invention 1.1 Exemplary Preparation Method of SSAD Hydrolyzate : S1: mixing a disulfide bond reducing agent and a first solvent to obtain a second solvent.
[0046] A suitable first solvent should contain substantially no ions, such as ultrapure water, deionized water, water for injection, pure water, and the like.
[0047] S2: mixing the freeze-dried powder of skin secretions of Siberian salamander with the second solvent to obtain a first mixed solution.
[0048] In fact, the mixing order of the disulfide bond reducing agent, the first solvent and the freeze-dried powder of skin secretions of the salamander (i.e., the step of obtaining the first mixed solution) is not specifically limited. For example, the first mixed solution can be obtained by adding and mixing the disulfide bond reducing agent, the first solvent and the freeze-dried powder of skin secretions of the salamander together, or by first mixing the disulfide bond reducing agent with the first solvent and then adding the freeze-dried powder of skin secretions of the salamander thereto, or by first mixing the freeze-dried powder of skin secretions of the salamander with the first solvent and then adding the disulfide bond reducing agent thereto, or by first mixing the disulfide bond reducing agent with the freeze-dried powder of skin secretions of the salamander and then adding the first solvent thereto. The ratio of the disulfide bond reducing agent, the first solvent and the freeze-dried powder of skin secretions of the salamander can be adjusted accordingly according to actual needs, and the present invention does not limit this. As an example, the mass ratio of the lyophilized powder of skin secretions of the salamander to the disulfide bond reducing agent may be 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1 or 3:1. The mass ratio of the first solvent to the lyophilized powder of skin secretions of the salamander may be 12:1, 11:1, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1 or 4:1. The concentration of the second solvent may be about 1%-5% (the specific value may be selected as about 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, w / w%) according to actual conditions). The lower limit (minimum value) of the mass ratio of the lyophilized powder of skin secretions of the salamander to the disulfide bond reducing agent may be 3:1. The lower limit (minimum value) of the mass ratio of the first solvent to the lyophilized powder of skin secretions of the salamander may be 4:1.
[0049] In some embodiments, the salamander includes one or more of the genera of Giant Salamander, Cryptobranchus, Stream Salamander, Hynomius, Babirus, Clawed Salamander, Fat Salamander, Pseudohyna, Myna, and Hyperborea. The skin is an important respiratory organ of the salamander, and is distributed with mucus glands and granular glands. The reason why the present invention selects the skin secretions of the Chinese giant salamander is that it can represent the mucus secreted by amphibians such as salamanders when stimulated. Electrical stimulation and skin scraping can promote the secretion of mucus.
[0050] S3: fully hydrolyzing the first mixed solution to obtain a second mixed solution.
[0051] The temperature conditions for the hydrolysis include 0-8°C (preferably 0-4°C). The hydrolysis time is related to factors such as the specific hydrolysis temperature, the concentration of the second solvent, and the concentration of the freeze-dried powder of the skin secretions of the salamander. In the temperature range of 0-8°C, the higher the temperature, the shorter the hydrolysis time; the higher the concentration of the second solvent, the shorter the hydrolysis time; the higher the concentration of the freeze-dried powder of the skin secretions of the salamander, the longer the hydrolysis time. The hydrolysis time may also be related to the specific type of disulfide bond reducing agent used. Therefore, the hydrolysis time can be adjusted accordingly according to actual needs, and the present invention is not limited to this. Exemplary hydrolysis times include 2-168 h, preferably 12-48 h. Mixing can be carried out in a mixing manner commonly used in the art, such as oscillation mixing, vortex mixing, etc. Preferably, S3 can be carried out in a low-temperature vacuum reactor, and the vacuum degree of the vacuum reactor is <5 kPa.
[0052] S4: centrifuging the second mixed solution and collecting the supernatant.
[0053] The specific conditions of centrifugation can be adjusted accordingly according to actual needs, and the present invention is not limited thereto. Exemplary centrifugation conditions include centrifugation at 4500 rpm for 10 min at 4°C.
[0054] S5: The supernatant is placed in a dialysis bag with a molecular weight cutoff of ≤1000 and fully dialyzed in the first solvent to obtain the hydrolyzate of skin secretions of Siberian salamander. The concentration of the hydrolyzate of skin secretions of Siberian salamander can be 5-7%.
[0055] The temperature conditions of the dialysis include 0-8°C (preferably 0-4°C). Preferably, a dialysis bag with a molecular weight cutoff of 500 or 1000 is used. The dialysis time is actually related to the treatment method during dialysis. For example, the dialysis time can be shortened by increasing the number of times the first solvent in the dialysis bag is replaced. Therefore, the dialysis time can be adjusted accordingly according to actual needs, and the present invention does not limit this.
[0056] Wherein, the disulfide bond reducing agent includes a specific disulfide bond reducing agent. In the present invention, "specific disulfide bond reducing agent" refers to a disulfide bond reducing agent that can reduce the intermolecular disulfide bonds in the protein or polypeptide to be reduced, while keeping the intramolecular disulfide bonds as unreduced as possible. The specific disulfide bond reducing agent includes tris(2-carboxyethyl)phosphine hydrochloride (TCEP-HCl). Of course, in the preparation method of the skin secretion hydrolyzate of the salamander provided by the present invention, it can also be used in combination with common protein denaturants / organic solvents known in the art, such as vitamin C, acetic acid, hydrochloric acid, β-mercaptoethanol, dithiothreitol, EDTA, urea, ethanol, acetone, guanidine hydrochloride, sodium dodecyl sulfate and sodium hydroxide and proteases (such as pepsin, trypsin, papain and subtilisin).
[0057] Furthermore, the method for preparing the hydrolyzate of skin secretions of Siberian salamander provided by the present invention may further include S6 concentrating the hydrolyzate of skin secretions of Siberian salamander to obtain concentrated hydrolyzate of skin secretions of Siberian salamander. The concentration of the concentrated hydrolyzate of skin secretions of Siberian salamander is ≥10%.
[0058] An exemplary concentration method includes placing the hydrolyzate of skin secretions of Siberian salamander into a concentration centrifuge tube with a molecular weight cut-off of ≤3K and centrifuging the hydrolyzate of skin secretions of Siberian salamander or concentrating the hydrolyzate by evaporation.
[0059] Preferably, any of the above steps is performed under vacuum or inert atmosphere.
[0060] In some embodiments, the preparation method comprises: placing the collected fresh skin secretions of giant salamander into a sterilized centrifuge tube, washing and centrifuging 3 times with PBS at 4°C, washing and centrifuging once with 5% acetic acid, and then pre-freezing in a -20°C refrigerator for 4 hours. After freeze-drying in a -80°C low-temperature freeze dryer for 24 hours, the mixture was crushed to 300 meshes using a frozen ball mill, and stored in a -20°C refrigerator for subsequent experiments. The lyophilized powder of giant salamander skin secretions, vitamin C, tris(2-carboxyethyl)phosphine hydrochloride (TCEP), and distilled water were mixed and reacted at a mass ratio of 10:5:5:100 for 24 hours. The supernatant was taken after centrifugation at 4000 rpm for 15 minutes, and the SSAD hydrolyzate was obtained after dialysis for 24 hours.
[0061] 1.2 Preparation of sponge materials The raw materials selected for preparing chitosan in the present invention are discarded shrimp shells and crab shells. Of course, other sources can also be selected, such as insects, shellfish, fungi, and algae. The shrimp shells and crab shells are washed with deionized water and ethanol, and then crushed using a high-speed mixer for standby use. The specific experimental steps are as follows.
[0062] 1.2.1 Deproteinization: 50 g of crushed shrimp and crab shells were added to 1 L of 1M NaOH solution, heated and stirred in an oil bath at 100°C for 1 h, and then washed with deionized water until neutral. This process was repeated twice, and then dried in an oven at 60°C to obtain deproteinized shrimp and crab shell powder.
[0063] 1.2.2 Decalcification: 50 g of deproteinized shrimp and crab shell powder was added to 1 L of 2M HCl solution, heated and stirred in a 60°C water bath for 1 h, and then washed with deionized water until neutral. This process was repeated twice, and dried in an oven at 60°C to obtain chitosan powder.
[0064] 1.2.3 Deacetylation: Take 40 g of the prepared chitosan and divide it into 4 equal parts, each with 10 g. One part was not treated and named CS-0. The remaining 3 parts were added with 500 mL of NaOH solution with a concentration of 40 wt.%, heated and stirred in a 100℃ oil bath for 30 min, 1 h and 4 h, respectively, and then washed with deionized water until neutral. Then dried in a 60℃ oven to obtain chitosan powders with different deacetylation degrees, which were named CS-0.5, CS-1 and CS-4 according to their deacetylation time. After measurement, the deacetylation degrees of CS-0.5, CS-1 and CS-4 were 38.4%, 61.2% and 85.1%, respectively.
[0065] 1.2.4 Preparation of chitosan micro-nanofibers: 10 g of chitosan powder was added to 1 L of deionized water and stirred for 12 h. Then, the chitosan was milled and peeled (mechanically peeled) at 1500 rpm using an ultrafine grinding mill (also known as an ultrafine particle crusher, MKCA6-2, Masuko Sangyo Co., Ltd., Japan). Grind 10 times at a grinding disc gap of 0, -10, -50 and -100 μm, and finally a chitosan dispersion uniformly dispersed in water was obtained. The obtained chitosan dispersion was centrifuged at a speed of 10000 rpm for 30 min, the lower layer of solid was collected, and a 3 wt.% chitosan dispersion was prepared with deionized water for use.
[0066] 1.2.5 Morphology analysis of micro-nano fibers: The chitosan dispersion was diluted to 0.1 wt.%, and then two drops were dropped onto the mica sheet and dried under natural conditions. Then, the mica sheet was treated with gold spraying, and the fiber structure was observed using a scanning electron microscope (SEM, Inspect F50, Netherlands) at a voltage of 20 kV. Figure 7 The SEM images show that the diameters of the chitosan micro-nano fibers all reach 30-60 μm, and there is no significant difference between the groups with different deacetylation degrees, which proves that the present invention can successfully prepare chitosan micro-nano fiber aqueous suspension using an ultrafine micro-mill.
[0067] 1.2.6 Preparation of sponge material: The prepared chitosan dispersion and SSAD hydrolyzate were diluted to 2 wt.%. 10 g of chitosan dispersion and SSAD hydrolyzate were added to a 50 mL beaker, mixed and stirred for 30 min, and then 5 mg of genipin was added to the beaker and stirred for 30 min. The obtained mixed solution was injected into a 48-well plate mold, precooled at 4°C for 2 h, frozen at -20°C for 12 h, and then placed in a freeze dryer for freeze drying for 24 h to obtain a sponge material. It was left to stand at room temperature for 1 week to allow it to be fully cross-linked. Then the well plate was filled with water to allow the sponge material to fully absorb water, and then placed in a -20°C environment for secondary freezing, and finally freeze-dried to obtain a fully cross-linked sponge material. The chitosan sponge without SSAD hydrolyzate as the control group was also prepared according to the above method, except that 10 g of SSAD hydrolyzate was replaced with deionized water, and the other steps were the same. The chitosan sponges without SSAD hydrolyzate were named CS 0, CS 0.5, CS 1, and CS4 according to the deacetylation time; the chitosan sponges with SSAD were named CS 0 + SSAD, CS 0.5 + SSAD, CS 1 + SSAD, and CS 4 +SSAD.
[0068] 1.2.7 Morphology and structure of sponge materials: The prepared sponge materials were cut under liquid nitrogen and then gold-sprayed. The cross-sectional structure of the sponge was observed using a scanning electron microscope (SEM, Inspect F50, Netherlands) at a voltage of 20 KV. Figure 8 The SEM images of chitosan sponges are shown. Each group of sponges has a good three-dimensional pore structure, which is conducive to the sponge's rapid absorption of water and blood.
[0069] 1.2.8 Shape recovery ability of sponge materials: Sponges with a diameter of 5 mm and a height of 10 mm were prepared for shape recovery time test. First, the sponge was compressed into a cylinder with a diameter of 5 mm and a height of 2 mm and placed in deionized water. When exposed to water, the sponge will recover its original shape in different time periods. The time required for the shape recovery of the sponge is recorded, which is the shape recovery time of the sponge. Each material was tested 3 times.
[0070] Table 1: Shape recovery time test results The results in Table 1 show that the compressed chitosan sponge can quickly recover to its original shape after being placed in water, indicating that it has excellent shape memory ability.
[0071] 1.2.9 Compression cycle test of sponge material: In order to characterize the cyclic stability of sponge material, a sponge with a diameter of 10 mm and a height of 10 mm was prepared and soaked in deionized water. After fully absorbing water, it was taken out. A universal mechanical testing machine (Instron 5567, USA) was used to perform 100 compression cycle tests at a compression rate of 10 mm / min, and the compression degree was 40% of the height. Fig. 9 The stress-strain curves of sponge CS 0.5 + SSAD after 100 compression cycles in liquid are shown. There is not much difference between the 100th compression curve and the first compression curve. Fig.10 The maximum stress changes of different sponges under different compression cycles are shown. The prepared sponge can still maintain a high initial stress after 100 compression cycles, which shows that the sponge disclosed in the present invention has good shape recovery ability and cycle stability. Fig.10 It can also be seen that after adding SSAD, the compressive strength and stress retention rate of CS + SSAD sponge are improved, especially the stability of CS 0 + SSAD is significantly increased compared with CS 0, which proves that the sponge with SSAD has better mechanical properties.
[0072] Embodiment 2 This embodiment uses a contact angle meter to test the static water contact angle of each sponge material. The surface contact angle reflects the liquid absorption capacity and speed of the material. This embodiment measures the surface contact angle to evaluate the hydrophilic and hydrophobic properties of the sponge material ( Figure 1 ). At 0 seconds, the contact angles of the experimental groups (i.e., CS 0, CS 0+SSAD, CS 0.5, CS 0.5+SSAD, CS 1, and CS 1+SSAD) were all less than 90°, indicating that the overall hydrophilicity of the sponge material was good. The hydrophilicity of CS 4 and CS 4+SSAD was slightly lower than that of the other groups, but both were able to completely absorb water after 15 seconds. The control group was an absorbent gelatin sponge used in clinical practice (Jiangxi Xiangen Medical Technology Development Co., Ltd., China), with a contact angle of approximately 125°.
[0073] Staphylococcus aureus suspension and Escherichia coli suspension were added to the surface of each sponge material. After incubation at 37°C for 2 hours, the bacteria were resuspended in sterile PBS and the quantitative resuspended bacterial solution was aspirated and inoculated on an agar plate. The culture was incubated overnight in a constant temperature incubator and the colonies were counted. Compared with gelatin sponge and gauze, the number of sponge colonies in the experimental group was reduced, and the antibacterial rate was about 40%-50% ( Figure 2A ). The direct contact antibacterial experiment showed that except for the gauze group, the other groups did not grow obvious colonies ( Figure 2B). Wherein, C0, C0.5, C1 and C4 represent CS 0, CS 0.5, CS 1 and CS 4 respectively; S0, S0.5, S1 and S4 represent CS 0 +SSAD, CS 0.5 + SSAD, CS 1 + SSAD and CS 4 + SSAD respectively.
[0074] Rat bone marrow mesenchymal stem cells (BMSCs) were cultured with sponge extracts of different concentrations, such as 1 mg / ml, 2 mg / ml, 5 mg / ml, and 10 mg / ml, and the cell proliferation was monitored for 7 consecutive days using the CCK8 method. The results showed that sponge extracts of different concentrations had no inhibitory effect on cell proliferation, and the cell survival rate was higher than 96%. Among them, the 4-hour deacetylated chitosan (CS 4) + SSAD group (CS 4 + SSAD) showed the most obvious pro-proliferation effect ( Figure 3 ).
[0075] Embodiment 3 In this example, the hemolytic activity of the sponge was detected by an in vitro hemolytic test (spectrophotometry). 10% red blood cell suspension was added to the test sample in sequence and mixed evenly. A mixture of red blood cell suspension and phosphate buffer solution (PBS) was taken as a negative control, and a mixture of red blood cell suspension and 0.5% Triton-X100 was taken as a positive control. The mixture was incubated at 37°C ± 0.5°C for 1 hour and observed.
[0076] The hemolysis rate is calculated as follows: centrifuge the incubated test tube, collect the supernatant, select a wavelength of 540nm, use distilled water as a blank control tube, and use a spectrophotometer to read the OD value of each tube. The hemolysis rate is calculated as follows: Hemolysis rate = (OD test tube - OD negative control tube) / (OD positive control tube - OD negative control tube)%. When the hemolysis rate is greater than 5%, it indicates that hemolysis has occurred.
[0077] The sponge material (chitosan composite SSAD sponge) provided by the present invention has a hemolysis rate of less than 5% for anticoagulated rat blood, and no hemolysis phenomenon ( Figure 4A ).
[0078] In this embodiment, the blood clotting index BCI (Blood Clotting Index) is used to evaluate the in vitro coagulation performance of the sponge material. Fresh blood is drawn from rats and added with an anticoagulant for later use. The sample to be tested is placed flat in the well plate, and after preheating at 37°C for 10 minutes, 50ul of recalcified whole blood is added to each well of the material. After incubation at 37°C for 1min, 2min, and 5min, 3mL of deionized water is added to each well, and shaken at 50rp / min at a constant temperature of 7°C for 5min. Then the solution is taken out and the OD value of each group is read using an ultraviolet spectrophotometer at a wavelength of 540nm. Set up a control: 50ul of recalcified whole blood is added with 3mL of deionized water, and the OD value measured at the same wavelength is used as a reference value. The calculation formula for the blood clotting index BCI is as follows: BCI=OD test group / OD control group%. The smaller the value of the coagulation index BCI, the better the coagulation effect of the corresponding material, and vice versa.
[0079] The coagulation index, red blood cell adhesion, and platelet adhesion all showed that the experimental group sponge was superior to the gauze and gelatin sponge control groups, but no significant differences were found among the experimental groups ( Figure 4B ).
[0080] This example also evaluates the in vivo hemostatic performance of the sponge material through an in vivo hemostatic experiment (rat liver injury bleeding model). A hole punch was used to create a 6 mm diameter defect in the rat liver. After 5 seconds of free bleeding, the hemostatic material was filled in and the amount of liver bleeding was calculated. Considering the effect of SSAD on the mechanical strength and elasticity of the sponge, the experimental group used chitosan SSAD composite sponge, and the control group used clinically commonly used hemostatic gauze and gelatin sponge. The CS1+SSAD group showed the best in vivo hemostatic performance ( Figure 5 ).
[0081] Embodiment 4 This example uses a rat alveolar defect model to explore the in vivo osteogenesis and site preservation effects of sponge materials. Eight-week-old female SD rats were taken, the first and second molars of the right maxillary were extracted, the alveolar septum was removed with a ball drill, and a 5×2×2 mm standard defect was prepared, and then the sponge was implanted for hemostasis.
[0082] Two months after the sponge material was implanted, the results showed that the width and height of the alveolar ridge and the number of trabeculae in the CS0+SSAD group were increased compared with the blank control group ( Fig. 6A ), the alveolar ridge contour is preserved ( Figure 6B ), among which the changes in alveolar ridge width and the number of trabeculae were statistically significant ( Figure 6C ).
[0083] Two months after the rat alveolar defect experiment, the samples were fixed and decalcified with 10% EDTA solution for one month before paraffin sectioning and staining. Fig.6DAs shown, there are trace amounts of sponge residues locally, indicating that the CS0+SSAD group is fully degraded in vivo.
[0084] The above results indicate that the sponge material provided by the present invention also has osteogenic properties and can match with tissues or bones or adjacent structures in the oral cavity after implantation, and can be applied to dentistry (e.g., site preservation) to enhance later implant restoration and aesthetic effects.
[0085] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. Use of a sponge material in preparing a bone hemostatic material for dental surgery, characterized in that: The sponge material is prepared by the following preparation method: S1: mixing chitosan powder with a first solvent and stirring to obtain a chitosan solution, wherein the chitosan powder includes chitosan that has not been deacetylated or chitosan that has been deacetylated; S2 mechanically treating the chitosan solution to obtain a first chitosan dispersion; the mechanical treatment comprises mechanically exfoliating the chitosan powder using an ultrafine particle crusher; S3 centrifuging the first chitosan dispersion and collecting the chitosan solid in the lower layer, and then resuspending the chitosan solid with the first solvent to obtain a second chitosan dispersion; S4: mixing and stirring the second chitosan dispersion and the hydrolyzate of skin secretions of Siberian salamander under neutral conditions, and then adding a cross-linking agent to obtain a third chitosan dispersion; S5 performing a first freeze-drying treatment on the third chitosan dispersion to obtain a first sponge material; S6 allowing the first sponge material to stand for sufficient cross-linking, and then adding the first solvent to the first sponge material so that the first sponge material fully absorbs water, thereby obtaining a first sponge material that fully absorbs water; S7 performing a second freeze-drying process on the first sponge material that has fully absorbed water to obtain a second sponge material; Wherein, the first solvent includes one or more of ultrapure water, deionized water, water for injection and pure water; and the bone hemostatic material is used during or after dental surgery.
2. The use according to claim 1, characterized in that The deacetylation treatment comprises adding the chitosan to 40 wt.% NaOH, heating in an oil bath at 100°C and stirring, washing to neutrality and drying; wherein the degree of deacetylation of the chitosan powder is controlled by the heating time.
3. The use according to claim 2, characterized in that The heating time includes 0.5-4 h.
4. The use according to claim 1, characterized in that The mechanical treatment method includes mechanically exfoliating chitosan powder using an ultrafine particle grinder, and grinding the chitosan under the conditions of a grinding disc gap of 0, -10, -50 and -100 μm respectively.
5. The use according to claim 4, characterized in that The number of millings includes 10 times.
6. The use according to claim 1, characterized in that The concentration of the second chitosan dispersion is 2 wt.%; the concentration of the hydrolyzate of skin secretions of the salamander is 2 wt.%.
7. The use according to claim 1, characterized in that The cross-linking agent includes genipin.
8. The use according to claim 1, characterized in that The first freeze-drying treatment includes precooling at 4°C for 2 hours, freezing at -20°C for 12 hours, and freeze-drying for 24 hours; the second freeze-drying treatment includes freezing at -20°C for 12 hours, and freeze-drying for 24 hours.
9. The use according to claim 1, characterized in that The dental surgery includes one or more of tooth extraction, site preservation, apical surgery, guided bone tissue regeneration, guided periodontal tissue regeneration, periodontal surgery, orthognathic surgery and bone defect repair.
10. The use according to claim 1, characterized in that The bone hemostatic material is used for implantation into a bone defect site.